Psychometric properties of parent reading belief inventory with a sample of Indonesian mothers - Hanggara Budi Utomo; Epritha Kurnia Wati; Widi Wulansari; Rosa Imani Khan (Institute of Advanced Engineering and Science, 2023)
The beliefs that parent currently have are increasingly attracting attention regarding the implementation of literacy for their children at home, was measured using parent reading belief inventory (PRBI) measuring tool developed by DeBaryshe and Binder. PRBI has not been adapted in Indonesia, making collaborative research difficult. Respondents in this study were mothers who had children aged 3-6 years old totally 177 respondents. Sampling technique with quota sampling. This research aims to develop a reliable and valid version of PRBI in Indonesia using International Test Commission guidelines. Data analysis using the second-order confirmatory factor analysis. The results showed that PRBI instrument was a valid and reliable instrument to measure the beliefs of parents in carrying out reading aloud activities with their children in Indonesia. Future research is expected to improve PRBI construct empirically based on the culture in each region, so that it can identify types of parents’ reading beliefs that implication children’s reading abilities.